Material flow control in sheet-bulk metal forming processes using blasted tool surfaces - Merklein, Marion; Löffler, Maria; Gröbel, Daniel; Henneberg, Johannes (Proceedings of the 5th International Conference on New Forming Technology, 2018)
Highly-integrated and closely-tolerated functional components can be produced by sheet-bulk metal forming which is the application of bulk forming operations on sheet metals. These processes are characterized by a successive and/or simultaneous occurrence of different load conditions such as stress and strain states which reduce the geometrical accuracy of the functional elements. Thus, one main challenge within sheet-bulk metal forming is the identification of methods to control the material flow and thus to improve the product quality. One suitable approach is to control the material flow by local modifications of the tribological conditions. Within this study requirements regarding the needed adaption of the tribological conditions for a specific sheet-bulk metal forming process were defined by numerical investigations. The results reveal that a local increase of the friction leads to an improved die filling of the functional elements. Based on these results abrasive blasting as a method to modify the tool surface and thus influencing the tribological behaviour was investigated. For the determination of the tribological mechanism of blasted tool surfaces, the influence of different blasting media as well as blasting pressures on the surface integrity and the friction were determined. The correlations between surface properties and friction conditions were used to derive the mechanisms of blasted tool surfaces.
LFT Import::2019-08-05 (2323)
Keywords: Cold forming; Surface modification; Tribology